Emotions of Indonesian Students in the International Learning Community for Example during the PASCH Youth Course - Sobara, Iwa (Nusantara Science and Technology Proceedings)
In this article, I examine the “Schools: Partners for the Future” (PASCH) program, its instruments youth language course with a focus on the emotions of Indonesian students, before, during and after participation in the PASCH youth language course. The pupils who are particularly successful and committed to teaching German at PASCH schools from all over the world are invited to the PASCH youth course in Germany. The course takes place annually for three weeks. The course participants have the opportunity to get to know Germany within three weeks. In addition, they meet in an open and lively exchange with other students from all over the world. Over 10,000 young people from PASCH partner schools in over 120 countries have completed German courses for children and young people as well as German exams. During the course, they not only learn German, but are also familiarized with everyday life in Germany. In addition, they also do other joint activities, such as trips/excursions, sports, etc. The present work deals with the emotions Indonesian students experience during the PASCH youth course and in which situations or events these emotions arise. An online questionnaire was used to collect the data. The different emotions expressed by the respondents include: joy, pride, curiosity, sadness, fear, nervousness, anger, disappointment, worry etc. Then all responses from the respondents were classified as positive or negative emotions according to the NRC Emotion Lexicon.